Older Veterans' Treatment Preferences: Psychotherapy and Self-Management Treatment Modalities. Issue 3 (27th May 2023) - Ma, Flora; Carlson, Chalise; Gomez, Rowena; Gould, Christine E.
ABSTRACT: Objectives: Self-management may help older Veterans with mental health challenges and can overcome barriers to traditional psychotherapy. However, the reasons underlying older Veterans' treatment preferences remain unknown. The current study investigated older Veterans' perspectives on psychotherapy and self-management. Methods: Seventy-four Veterans ≥ 60 years old were included in this mixed methods study. Participants provided rationale(s) after ranking their preferences for psychotherapy and four self-management modalities. Logistic regressions examined whether depressive and anxiety symptom severity contributes to preferences. Qualitative analyses were conducted to investigate reasoning for preferences. Results: Most participants preferred psychotherapy (64.9%) over self-management (35.1%). Logistic regressions showed that depressive and anxiety symptom severity was not significantly associated with preferences. Qualitative analyses revealed that past experience and access-related barriers were underlying the preferences. Themes unique to psychotherapy included the availability of emotional support and the process of information sharing. In contrast, ease of access was associated with self-management. Conclusions: Older Veterans preferred psychotherapy to receive support and to develop trust in meeting their goals. Clinical Implications: Older Veterans' needs point to the importance of providers' consideration of a person-centered approach and treatment collaboration. Notably, Veterans' preference for psychotherapy highlights the importance and need for human support in addition to self-management tools.